ANALISIS PENGARUH ESG DISCLOSURE, GREEN FINANCING, DAN KINERJA SAHAM TERHADAP PREFERENSI INVESTOR (STUDI PADA SAHAM SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2024) - Nur Rista Rista; Any Eliza; Anggun Okta Fitri (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2026)
Abstract This study aims to examine the effect of Environmental, Social, and Governance (ESG) Disclosure, Green Financing, and Stock Performance on Investor Preference in Sharia-compliant stocks listed on the Indonesia Stock Exchange during the 2019–2024 period. The research employed a quantitative approach using secondary data obtained from annual reports, sustainability reports, and official publications from the Indonesia Stock Exchange, the Financial Services Authority (OJK), Yahoo Finance, and RTI Business. The sample consisted of 20 Sharia-listed companies selected through purposive sampling, resulting in 120 panel data observations. Data were analyzed using panel data regression with the Common Effect Model (CEM) in EViews 13. The results indicate that ESG Disclosure has a negative but insignificant effect, while Green Financing and Stock Performance have positive but insignificant effects on Investor Preference. Simultaneously, all variables have no significant effect. These findings suggest that investor preference is influenced more by Sharia compliance, risk perception, market sentiment, and investor characteristics than by sustainability and financial performance. Keywords: ESG Disclosure, Green Financing, Stock Performance, Investor Preference, Sharia Stocks.